Polyacrylonitrile-Chalcogel Hybrid Sorbents for Radioiodine Capture - Riley, Brian J; Pierce, David A; Chun, Jaehun; Matyáš, Josef; Lepry, William C; Garn, Troy G; Law, Jack D; Kanatzidis, Mercouri G (Environmental science & technology, 2014)
Powders of a Sn2S3 chalcogen-based aerogel (chalcogel) were combined with powdered polyacrylonitrile (PAN) in different mass ratios (SnS33, SnS50, and SnS70; # = mass% of chalcogel), dissolved in dimethyl sulfoxide, and added dropwise to deionized water to form pellets of a porous PAN-chalcogel hybrid material. These pellets, along with pure powdered (SnSp) and granular (SnSg) forms of the chalcogel, were then used to capture iodine gas under both dynamic (dilute) and static (concentrated) conditions. Both SnSp and SnSg chalcogels showed very high iodine loadings at 67.2 and 68.3 mass%, respectively. The SnS50 hybrid sorbent demonstrated a high, although slightly reduced, maximum iodine loading (53.5 mass%) with greatly improved mechanical rigidity. In all cases, X-ray diffraction results showed the formation of crystalline SnI4 and SnI4(S8)2, revealing that the iodine binding in these materials is mainly due to a chemisorption process, although a small amount of physisorption was observed.